Study of structural phase transition of HfO2 at high pressure. (2016) - Mandal, G.; Jana, R.; Saha, P.; Das, P.
Abstract: High pressure room temperature Raman spectroscopy measurements on hafnium oxide were performed up to 40 GPa using Diamond Anvil Cell. Phase transitions were observed at about 5.6 GPa with appearance and disappearance of certain Raman modes. Also it goes to amorphous state at high pressure. The pressure evolutions of the Raman modes are not found to be linear. The non-linear pressure evolutions of modes indicate to an initial large compression in the system.